Edukasi Upaya Pencegahan Pelecehan Seksual pada Remaja di Lingkungan Sekolah Bhakti Indonesia Medika - Rhadika Wahyu Kurnia Ningrum; Alvy Nur Hidayati; Ho Soyen (Jurnal Pengabdian Bidang Kesehatan, 2026)
Sexuality education is crucial for equipping adolescents and fostering healthy, responsible behavior. Lack of knowledge and understanding regarding sexuality education can increase the risk of sexual behavior, which can impact physical and mental health, and reduce concentration during learning. This activity aims to increase the knowledge of students at SMK Bhakti Indonesia Medika in Pangkalanbun Regency regarding education on preventing sexual harassment in the school environment. The outreach activity was conducted in May 2026 with 43 students aged 15-16 years, using a pretest-posttest method, leaflets, and PowerPoint presentations. The results showed an increase in the average student knowledge score from 50 to 95 after the education. The majority of students were 16 years old, and some had boyfriends. These findings indicate that the education provided in schools is very effective and useful as a warning to take the first step in preventing sexual harassment in the school environment for adolescents. This education can be recommended for regular replication to strengthen a safe and responsive school culture to child protection issues.